Analisis Kadar Tanin Ekstrak Etanol Kulit Batang Kemiri (Aleurites moluccana (L.) Willd) dengan Metode Titrimetri - Sofiya Maulida; Ali Rakhman Hakim; M. Sobirin Mohtar (LPPM Universitas Sari Mulia, 2020)
Introduction: Plants have a great potential to be used as traditional medicine, so it is necessary to standardize realated compounds responsible for pharmacological activities or secondary metabolite compounds of a plant. One of medicinal plants is candlenut, this is plant has many uses in almost all parts of the plant. Candlenut stem bark has been used as traditional medicine by the community in Muara Langon village, Paser district, East Kalimantan to treat hypercholesterolemia. Objective: To know the candlenut stem bark ethanol extract containing flavonoid, saponin, tannin compounds and knowing the levels of tannin compounds contained in the sample. Methods: Extraction was carried out by maceration method. Qualitative analysis was carried out by phytochemical screening tests for flavonoid, saponin and tannin compounds by the tube method. Quantitative analysis was carried out by determining the levels of tannin compounds using the titrimetry method by permanganometric titration. Results: The extraction of 500 grams candlenut stem bark and 4 liters ethanol 70% sovent obtained was the extract rate od 4,022%. The results of the qualitative analysis by phytochemical sreening test showed that the candlenut stem bark ethanol extract is positively contained flavonoid, saponin and tanin compounds. The result of quantitative analysis with titrimetry method obtained levels of tannin compounds in the candlenut stem bark ethanol extract is 5,40598 %. Conclusion: The candlenut stem bark ethanol extract contained flavonoid, saponin and tanin compounds and tannin compound levels is 5,40598 %. Keywords: Candlenut stem bark, Tannin levels, Titrimetry.